Multiphase change materials for energy storage application in buildings - Darkwa, Jo; Su, Weiguang (American Institute of Aeronautics and Astronautics, 2017)
Experimental study has been carried out towards the development of a multiphase change material (MCM) by combining two fabricated microencapsulated phase change materials (MEPCM-oct and MEPCM-eic) samples. The study also covered the characterization of the developed samples for their thermal properties. For the purpose of validation the thermal properties of the developed MCM sample were compared with that of the core components. The developed MCM sample achieved a combined energy storage capacity of 186 kJ/kg with two melting temperatures of 23.4oC and 34.5oC. Even though the two melting temperatures of the MCM were slightly reduced by 0.18℃ and 0.48℃ in comparison with the MEPCM-oct and MEPCM-eic respectively, their mean energy storage capacities were in perfect agreement. The study has therefore shown that it is possible to overcome some of the scientific barriers towards the development of multiphase change materials but further investigations are needed to enhance overall thermal response.